O assédio moral no contexto universitário: uma análise à luz da perspectiva psicossocial - Souza, Maria Carolina Lima de (Brasil, 2022)
The moral harassment is a complex and multicausal phenomenon, that have repercussions in several aspects of the daily life. In the work environment, it can be even more aggressive, and it’s effects on the victim’s life can go beyond the psychosocial. The occurrence of this kind of violence inside the universities is expressive, but sometimes it gets silenced due to the of management models and the disputes for power. Based on this scenery and its characteristics, this paper intent is to discuss moral harassment at university context, associating the theory to a study of a case following the psychosocial approach. The objectives follow four main cores: understand how this phenomenons can occur, present the characteristic elements of this phenomenon and the way it happen at the public superior school system, discuss the work of a commission to prevent and combat; and propose strategies of prevention and promotion of mental health at the work environment.